Potensi Sel Punca Mesenkim dalam Penyembuhan Luka Menggunakan Scaffold Nanofiber: Mini Review - Rofaani, Elrade; Astirin, Okid Parama; Purba, Priskila Natasya Rambe (Jurnal Biomedika dan Kesehatan, 2025)
Currently, the use of mesenchymal stem cells (MSCs) in cell therapy is growing as a means to repair damaged cells. MSCs are multipotent stem cells capable of differentiating into a variety of specialized cell types across multiple tissues. Adipose tissue, bone marrow, umbilical cord, and placenta are possible sources of MSCs. MSCs secrete a bioactive secretome that affects skin cells by mediating the actions of growth factors and cytokines. MSCs can actively contribute to wound healing through several phases, including promoting fibroblast migration, neovascularization, secreting anti-inflammatory cytokines, and re-epithelialization. To improve therapeutic effectiveness, appropriate biomaterials were incorporated into nanofiber scaffolds to mimic the natural extracellular matrix and attract fibroblasts into the skin layer. The purpose of this review is to evaluate research on the use of MSCs with various nanofiber scaffolds in the wound healing process in vitro. The review finds that several natural and synthetic polymers used as scaffold materials are biocompatible, thereby increasing the healing potential of wound tissue. MSCs, when co-cultured in nanofiber scaffolds, activate several mechanisms, including the expression of genes and growth factors related to wound healing. It is concluded that the use of biopolymers in MSC-seeded scaffold designs can contribute to the enhancement of wound healing and tissue regeneration.